Initial study for creating linearly moving vibrotactile sensation on mobile device - Jongman Seo; Seungmoon Choi (2010 IEEE Haptics Symposium, 2010)
This paper investigates the feasibility of creating spatially moving vibrotactile sensations using two vibrotactile actuators in a mobile device. The idea is based on well-known tactile illusions of apparent tactile motion and ¿phantom¿ sensation. The phantom sensation refers to a perceptual phenomenon where spatially separated vibrotactile actuators that stimulate different skin zones induce a single tactile sensation midway between the two stimulation points. We tested whether such sensation can also be elicited in a mobile device via a psychophysical experiment that employed an open response paradigm. Experimental conditions differed in vibration rendering method, signal duration, and sensation movement direction. The subjects answered the perceived positions and intensities of vibrotactile sensations by drawing graphs with respect to time. The results demonstrated that such ¿vibrotactile flow¿ can be reliably produced in a mobile device and that a performance trade-off exists depending on the method and signal duration used for rendering. The findings of this paper can be applied to the user interface design of a mobile device with enriched vibrotactile sensations and an improved information transfer bandwidth.